Transesterification of palm oil by an immobilized rhizomucor miehei lipase / A.Z. Hazlina and H.M. Ghazali - A.Z., Hazlina; H.M., Ghazali (2004)
Enzymatic transesterification of RED palm oil was studied. Transesterification was done by reacting RBD palm oil with an immobilized R. miehei lipase in water-saturated hexane at various reaction temperatures. Analyses were done on the transesterified oils triglyceride composition and its melting characteristics using HPLC and DSC, respectively. Transesterification increased the concentration of MMM, OOL, MMP, 000 and PPS at reaction temperatures of 50°C and 60°C. At 30°C and 40°C, MMM, OOL, MMP was observed to increase. The degree of transesterification was between 18% and 46%, which coincided with the degree of hydrolysis between 1.9% and 2.5%. Percentage of triglycerides retained after transesterification was between 83% and 85%. Lowest transesterification rate was noted when palm oil was transesterified at 30°e. Generally, the heating thermogram of palm oil transesterified at different reaction temperatures showed three different regions compared to the non- transesterified palm oil. One new peak was found to be sandwiched between the low-T and high-T peaks. However, this peak was not observed in palm oil transesterified at 60°e. One peak at the high-T region was also observed for heating thermogram of oil transesterified at 60°C, compared to two peaks formed for the other reaction temperatures studied. The transesterified oils started to melt at between -25.74°C and -24.53°C and totally melted at between 43°C and 45.5°C. The non- transesterified oil started to melt at -24.65°C and totally melted at 43.2°C.